2013
DOI: 10.1038/ejcn.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Severe vitamin C deficiency in a critically ill adult: a case report

Abstract: Scurvy, a severe form of vitamin C deficiency, killed scores of people until its cause and treatment were firmly established at the end of the eighteenth century. Since then, cases have surged periodically around the world, mostly in developing countries and during times of war and famine. In developed countries, scurvy is still endemic and evidence is growing that vitamin C deficiency might affect up to 30 percent of the population. Low socio-economic status, alcoholism, severe psychiatric illness leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 7 publications
(6 reference statements)
0
32
0
1
Order By: Relevance
“…Children in particular suffer from severe lower limb pain, as evidenced by numerous case reports in the literature [12–16]. There have also been reports of adults and the elderly experiencing musculoskeletal pain due to severe vitamin C deficiency [17, 18]. Scurvy-related pain appears to be primarily due to bleeding into the musculoskeletal tissues, which can become so debilitating that patients are unable to walk [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children in particular suffer from severe lower limb pain, as evidenced by numerous case reports in the literature [12–16]. There have also been reports of adults and the elderly experiencing musculoskeletal pain due to severe vitamin C deficiency [17, 18]. Scurvy-related pain appears to be primarily due to bleeding into the musculoskeletal tissues, which can become so debilitating that patients are unable to walk [7].…”
Section: Introductionmentioning
confidence: 99%
“…Those already malnourished are more prone to this development [14]. ” Similarly, others have reported painful scurvy symptoms following confirmed or suspected respiratory infection [18, 19], stating that “sepsis of either digestive or pulmonary origin, leading to sustained metabolic demand, might have acted as a precipitating factor [18]. ” As such, it is possible that other hospital-associated pain may be partly due to vitamin C deficiency, which is relatively prevalent in hospital settings [2023].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans cannot synthesize vitamin C, so it is crucial to delivering it through the diet. Palliative care patients very often face with vitamin C deficiency (plasma vitamin C concentrations < 11 µmol/L) [25] especially because it has been demonstrated that patients under oxidative stress, for example in surgical intensive care, have greater requirements for vitamin C [26]. The administration of anti-cancer drugs may induce a decrease in patients' vitamin C concentrations [27][28][29].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Vitamin C deficiency is rare in developed countries; however, in unique clinical situations where intake may be impaired, its associated morbidity and mortality should be taken in consideration. Most of the literature describing vitamin C deficiency is dated ; however, acquired vitamin C deficiency has been reported more recently in several patient populations, including patients with anorexia nervosa, cystic fibrosis, those on long‐term tube feedings, and those with perceived food allergies, among others. In this report, we pose another population to include in this group at increased risk for the development of scurvy.…”
mentioning
confidence: 99%